1986
DOI: 10.1007/bf02907994
|View full text |Cite
|
Sign up to set email alerts
|

Complete amino acid sequence of the α-amylase/subtilisin inhibitor from barley

Abstract: The complete amino acid sequence of the ct-amylase/subtilisin inhibitor (BASI) isolated from barley has been determined by Edman degradation using spinning cup as well as gas-phase sequencing. Necessary fragments have been obtained from cleavage with cyanogen bromide, hydroxylamine, formic acid, clostripain, and streptococcal protease V8. The molecule consists of a single peptide chain of 181 residues with two disulphide bonds and with a molecular weight of 19,865. Homology is demonstrated with other members o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 32 publications
4
53
0
Order By: Relevance
“…Triumf), each from Carlsberg Maltings. The protein concentrations were determined by amino acid analysis of acid hydrolysates (6 N HCI, 110°C, 24 h) using an LKB model Alpha Plus amino acid analyzer, or spectrophotometrically at 280 nm using e = 2.6 x 104 M -~ .cm -t for BASI [1,7] and e = 1.13 x 105 M -l .cm -1 for AMY2 [161. Insoluble blue starch was from Pharmacia, Uppsala, Sweden.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triumf), each from Carlsberg Maltings. The protein concentrations were determined by amino acid analysis of acid hydrolysates (6 N HCI, 110°C, 24 h) using an LKB model Alpha Plus amino acid analyzer, or spectrophotometrically at 280 nm using e = 2.6 x 104 M -~ .cm -t for BASI [1,7] and e = 1.13 x 105 M -l .cm -1 for AMY2 [161. Insoluble blue starch was from Pharmacia, Uppsala, Sweden.…”
Section: Methodsmentioning
confidence: 99%
“…Barley seeds contain a bifunctional a-amylase/subtilisin inhibitor, (BASI) of Mr 19,865 [1,2]. Based on sequence similarities it belongs to the soybean trypsin inhibitor (Kunitz) family [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these inhibitors, PKI-2 appears to have a somewhat broad specificity, with limited but significant activity against both trypsin and chymotrypsin. Three Kunitz-type subtilisin inhibitors from monocot seeds, barley (22), wheat (9), and rice (22), have been characterized and sequenced. The inhibitors from barley and wheat are bifunctional and possess activity against insect amylases (3).…”
Section: Assays Of Proteinase Inhibitionmentioning
confidence: 99%
“…The elution by a linear sodium chloride gradient exhibited 5 distinct major peaks of proteins (data not shown). Analysis of the protein components of these peaks by SDS-PAGE revealed that in one peak (called III), at least 80% of the total amount of the protein C was co-eluted with the barley a-amylase/subtilisin inhibitor, BASI (20). This "III" fraction, consisting mainly of the two proteins, was further purified by CM-52 cation exchange chromatography as shown in Figure 1.…”
Section: Isolation Of Barley Protein Cmentioning
confidence: 99%